2013
DOI: 10.1517/17425247.2013.860131
|View full text |Cite
|
Sign up to set email alerts
|

Fisetin-loaded nanocochleates: formulation, characterisation,in vitroanticancer testing, bioavailability and biodistribution study

Abstract: In this research article, we focused on lipid-based supramolecular assembly 'nanocochleates' composed of negatively charged phospholipids and divalent cation as drug carrier for systemic delivery system and discussed their formulations, optimisation, characterization, in vitro and in vivo performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 42 publications
1
60
0
2
Order By: Relevance
“…Bothiraja et al [12] examined the bioavailability of fisetin-loaded nanocochelates which are lipid-based supramolecular assemblies containing negatively charged phospholipid and a divalent cation. Pharmacokinetic studies in mice showed that there was a sustained release of fisetin at physiological pH and when nanocochleates were administered ip, there was low tissue distribution and massive increase (141-fold) in relative bioavailability [12].…”
Section: Bioavailability and Pharmacokinetics Of Fisetinmentioning
confidence: 99%
“…Bothiraja et al [12] examined the bioavailability of fisetin-loaded nanocochelates which are lipid-based supramolecular assemblies containing negatively charged phospholipid and a divalent cation. Pharmacokinetic studies in mice showed that there was a sustained release of fisetin at physiological pH and when nanocochleates were administered ip, there was low tissue distribution and massive increase (141-fold) in relative bioavailability [12].…”
Section: Bioavailability and Pharmacokinetics Of Fisetinmentioning
confidence: 99%
“…Previously, attempts have been made for the delivery of FST using lipid-based carriers and chelating agents such as calcium (Bothiraja et al, 2014). However, these attempts were limited to intraperitoneal and intravenous administration only.…”
Section: Introductionmentioning
confidence: 99%
“…Fisetin has been formulated in nanoemulsions [6], nanocochleates [7], liposomes [8,9] and cyclosophoroase dimer complexes [10].…”
Section: Introductionmentioning
confidence: 99%